A basic helix-loop-helix transcription factor CabHLH113 positively regulate pepper immunity against Ralstonia solanacearum. (July 2021) - Hussain, Ansar; Noman, Ali; Arif, Muhammad; Farooq, Shahid; Khan, Muhammad Ifnan; Cheng, Ping; Qari, Sameer H.; Anwar, Muhammad; Hashem, Mohamed; Ashraf, Muhammad Furqan; Alamri, Saad; Adnan, Muhammad; et al.
Abstract: Pepper's ( Capsicum annum ) response to bacterial pathogen Ralstonia solanacearm inoculation (RSI) and abiotic stresses is known to be synchronized by transcriptional network; however, related molecular mechanisms need extensive experimentation. We identified and characterized functions of CabHLH113 -a basic helix-loop-helix transcription factor-in pepper immunity to R. solanacearum infection. The RSI and foliar spray of phytohormones, including salicylic acid (SA), methyl jasmonate (MeJA), ethylene (ETH), and absicic acid (ABA) induced transcription of CabHLH113 in pepper. Loss of function of CabHLH1 13 by virus-induced-gene-silencing (VIGS) compromised defense of pepper plants against RSI and suppressed relative expression levels of immunity-associated marker genes, i.e., CaPR1, CaNPR1, CaDEF1, CaHIR1 and CaABR1 . Pathogen growth was significantly increased after loss of function of CabHLH113 compared with un-silenced plants with remarkable increase in pepper susceptibility. Besides, transiently over-expression of CabHLH113 induced HR-like cell death, H2 O2 accumulation and up-regulation of defense-associated marker genes, e.g. CaPR1, CaNPR1, CaDEF1, CaHIR1 and CaABR1. Additionally, transient over-expression of CabHLH113 enhanced the transcriptional levels of CaWRKY6, CaWRKY27 and CaWRKY40. Conversely, transient over-expression of CaWRKY6, CaWRKY27 and CaWRKY40 enhanced the transcriptional levels of CabHLH113 . Collectively, our results indicate that newly characterized CabHLH1 13 has novel defense functions in pepper immunity against RSI via triggering HR-like cell death and cellular levels of defense linked genes. Highlights: Pepper's response to Ralstonia solanacearm inoculation (RSI) was tested. The functions of CabHLH113 were identified and characterized. Pathogen growth was significantly increased after loss of function of CabHLH113 . Transiently over-expression of CabHLH113 induced HR-like cell death. Newly characterized CabHLH1 13 has novel defense functions in pepper immunity against RSI.